Artistic-Pragmatic Function of Language Units in Poetic Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is aimed at studying the pragmastilistic features of poetic texts and pays special attention to the identification of artistically characterized language units. The process of analysis in the study is not limited to the study of formal and grammatical aspects, but also includes linguistic means enriched with poetic content. From this point of view, in-depth study of the text falls within the sphere of linguopoetics.